The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/8091963
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s Disease-Related Risk of Suicide and Effect of Deep Brain Stimulation: Meta-Analysis

Abstract: Background. Previous studies investigated the risk of suicide in patients with Parkinson’s disease (PD) but reported discrepant results. Deep brain stimulation (DBS) is an effective therapy for PD, while its effect on suicide risk has seldom been researched. This meta-analysis aimed to estimate the risk of suicide and/or suicidal ideation in PD patients and in PD patients who underwent DBS. Methods. Relevant articles published in the PubMed or EMBASE or CNKI database from 1990 to December 2019 were sourced, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Another contentious association is reported between DBS and increased suicide risk. A recent meta-analysis of patients with PD after DBS showed similar rates of suicidal behavior (1%) as found in our study, while another study demonstrated an increased rate of completed suicide in patients with PD post-DBS compared with general population . However, there has been no convincing evidence that DBS increases the risk of suicide compared with pharmacotherapy alone .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Another contentious association is reported between DBS and increased suicide risk. A recent meta-analysis of patients with PD after DBS showed similar rates of suicidal behavior (1%) as found in our study, while another study demonstrated an increased rate of completed suicide in patients with PD post-DBS compared with general population . However, there has been no convincing evidence that DBS increases the risk of suicide compared with pharmacotherapy alone .…”
Section: Discussionsupporting
confidence: 82%
“…54 However, there has been no convincing evidence that DBS increases the risk of suicide compared with pharmacotherapy alone. 54 In either case, physicians must appreciate the increased suicide risk in all patients with PD patients and care should be taken when considering patients for DBS or other treatment options. Monitoring and managing suicidality should be a priority, especially for those with psychiatric risk factors, such as preexisting depression or other mood disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Prevalence of suicide risk in PD varies widely depending on the population (decreased or unchanged in USA, Denmark, Finland, and Canada but increased in South Korea, England, Netherlands, and Sweden); however, cultural differences or differences in the standard management of PD and PD depression could explain at least in part these findings. 14 Some factors have been associated with an increased risk of suicide in PD, such as deep brain stimulation or dopamine agonists withdrawal, 16,17 whereas mechanisms such as alterations in immune function and serotonin neurotransmission have been implicated in suicide in the general population. 18,19 According to the literature, aggressive management of depression could be the best approach for suicide prevention, 15 but studies focused on suicide in PD are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson’s disease (PD) is a neurodegenerative disorder that affects up to 3% of adults over 65 years of age and is primarily characterized by motor symptoms including bradykinesia, resting tremor, and muscle rigidity [ 1 ]. In addition to motor symptoms, PD patients often experience cognitive impairment, behavioral changes, and mood disorders such as depression [ 2 ].…”
Section: Introductionmentioning
confidence: 99%